Organic, inorganic and nanoparticles of Se, Zn and Mn in early weaning diets for gilthead seabream (Sparus aurata; Linnaeus, 1758). (18th June 2016) - Izquierdo, Marisol S; Ghrab, Wafa; Roo, Javier; Hamre, Kristin; Hernández‐Cruz, Carmen M; Bernardini, Giovanni; Terova, Genciana; Saleh, Reda
Abstract: Levels of the oxidative stress‐related minerals selenium (Se), zinc (Zn) and manganese (Mn) that should be supplied in microdiets for marine fish larvae depend on the availability of the molecular form of these minerals. The objective of this study was to determine how effectively Se, Zn and Mn in organic, inorganic and nanoparticle forms promote larval performance and bone development. Microdiets supplemented with Se, Zn and Mn were fed for 24 days to 20 dah seabream larvae. Microdiets without Se, Zn and Mn supplementation were associated with poor growth, low bone mineralization and a high incidence of anomalies in the branchial arches. Including Zn, Mn and Se in an amino acid chelate organic form promoted maximum larval growth, increased body lipid reserves, enhanced early mineralization and prevented branchial arches anomalies. In contrast, feeding with inorganic forms of these minerals was less effective than organic minerals in improving larval weight or bone mineralization in comparison to the non‐supplemented diet. Moreover, the larvae were less resistant to stress, and fish showed higher bone anomalies in the pre‐hemal region. Adding Zn, Mn and Se in the form of nanometals did not enhance growth, but improved stress resistance and bone mineralization. The study showed the need to supplement seabream with early weaning diets based on squid meal and krill oil with one or more of the antioxidant minerals, to promote larval growth, bone mineralization and prevention of skeleton anomalies, organic minerals being more effective than inorganic forms and nanometals in promoting mineralization and stress resistance.